Lessons Learned from a Pandemic: Covid-19 and Substance Use - Torun, Hüseyin Ozan; Coşkunol, Hakan (Addicta: The Turkish Journal on Addictions, 2021)
The aim of this review is to investigate the effects of the pandemic on substance use disorders and psychiatric care. Coronavirus disease 2019 (COVID-19) is a severe respiratory syndrome caused by coronavirus 2 (SARS-CoV-2) and has become a global pandemic rapidly. As a result of anxiety and fear for their health and careers, and the life they are forced to live in an unfamiliar lifestyle, the condition of people with psychological issues may have deteriorated during the pandemic. Many experts suggest that the pandemic may contribute to a global rise in drug use disorders as individuals deal with the anxiety and uncertainty caused by the pandemic. Some studies show that over half of the participants either started using or increased the use of medications or substances, most commonly alcohol and sleep aids, as a result of the COVID-19 pandemic. The COVID-19 pandemic is disproportionately affecting particularly vulnerable individuals who use drugs. Together with other factors, both comorbid diseases in substance use disorders (SUDs) (especially cardiopulmonary diseases and associated risk factors) and drugdrug interactions (between abused substances or SUD treatment medicines and COVID-19 treatment drugs) can lead to further complications for people with SUDs when they experience a COVID-19 infection. Also, during the COVID-19 pandemic, some hospitals could not accept SUD patients; partial hospital programs have adjusted their enrollment criteria, denying or delaying acceptance. For these reasons, there have been changes in the treatment processes. Telehealth has become much more important. Telehealth, also often called as telemedicine, is characterized by telecommunications technology as the delivery of health care over a distance.